Trend in rifampicin-, multidrug- and extensively drug-resistant tuberculosis in Italy, 2009–2016. Issue 1 (19th July 2018) - Mustazzolu, Alessandro; Borroni, Emanuele; Cirillo, Daniela Maria; Giannoni, Federico; Iacobino, Angelo; ,; Fattorini, Lanfranco
Tuberculosis (TB) caused by strains of Mycobacterium tuberculosis that are rifampicin-resistant (RR), multidrug-resistant (MDR) (strains resistant to at least isoniazid and rifampicin) or extensively drug-resistant (XDR) (MDR strains resistant to any fluoroquinolone (FQ) and to at least one second-line injectable drug (SLID): kanamycin, capreomycin or amikacin) is a major threat to TB control globally. All three groups require treatment with second-line drugs (SLDs) [1]. We previously reported that MDR- and XDR-TB in Italy occurred mostly in foreign-born persons (FBPs) [2, 3], but no major information on RR, MDR or XDR trends in FBPs and Italian-born persons (IBPs) were shown. Here, we documented these trends from 2009 to 2016 (figure 1). In Italy, rifampicin-resistant and MDR-TB were high in foreign-born persons, but decreased from 2009 to 2016 http://ow.ly/MrIy30jNjFj